Scenario-Based Modelling of Waste Generation and Separation Potential at the Municipal Level - Smejkalová, Veronika; Šomplák, Radovan; Pluskal, Jaroslav; Němcová, Lucie (My University, 2025)
Efforts to save the environment and primary resources have led to the release of a Circular Economy Package by the EU. One of the basic principles is to turn waste into raw material and use the potential hidden in waste. For a sustainable waste management system, it is necessary to build an adequate infrastructure for material recovery and energy recovery of waste. This paper presents a modelling approach that supports the allocation of national waste separation targets to municipalities based on their local potential. With regard to the dynamic development of waste management, the waste produced will likely be affected by interventions in the future. This aspect is modelled using scenarios. The uniqueness of the presented modelling approach is mainly in the use of the properties of the hierarchical data structure, the coherence of the process at the national and regional levels needs to be ensured. Potential for increasing waste separation is identified, it is assumed that all municipalities contribute to increasing the separation efficiency until the separation potential is fulfilled. Three national scenarios are developed for the Czech Republic in the case study. Separation rates are defined individually for selected fractions. While the separation rate is not equal to the official recycling rate, the ambitious separation rate values in the third scenario (e.g. 80% for plastics and biowaste) indicate the potential to support future CEP recycling targets. The results support strategic waste management planning and infrastructure development tailored to regional conditions.

Efforts to save the environment and primary resources have led to the release of a Circular Economy Package by the EU. One of the basic principles is to turn waste into raw material and use the potential hidden in waste. For a sustainable waste management system, it is necessary to build an adequate infrastructure for material recovery and energy recovery of waste. This paper presents a modelling approach that supports the allocation of national waste separation targets to municipalities based on their local potential. With regard to the dynamic development of waste management, the waste produced will likely be affected by interventions in the future. This aspect is modelled using scenarios. The uniqueness of the presented modelling approach is mainly in the use of the properties of the hierarchical data structure, the coherence of the process at the national and regional levels needs to be ensured. Potential for increasing waste separation is identified, it is assumed that all municipalities contribute to increasing the separation efficiency until the separation potential is fulfilled. Three national scenarios are developed for the Czech Republic in the case study. Separation rates are defined individually for selected fractions. While the separation rate is not equal to the official recycling rate, the ambitious separation rate values in the third scenario (e.g. 80% for plastics and biowaste) indicate the potential to support future CEP recycling targets. The results support strategic waste management planning and infrastructure development tailored to regional conditions.
Scenario-Based Modelling of Waste Generation and Separation Potential at the Municipal Level
Keywords: Waste production forecasting; Waste separation; Projection modelling; Scenario-based modelling; Municipal-level planning; Circular Economy Package; Waste production forecasting; Waste separation; Projection modelling; Scenario-based modelling; Municipal-level planning; Circular Economy Package